(untitled) (Research, Society and Development, 2022)
The environmental issue is closely linked to chemical concepts and the high relevance of its approach in all spheres of society. It is known that, for effective and meaningful teaching of Chemistry, it is necessary to understand and test new tools to improve student learning. In this sense, gamification can be a good strategy in teaching. The usability of the didactic game as a pedagogical tool and its contributions to the teaching and learning process must be verified using adequate analysis. From this perspective, the objective of this work was to develop a computer game using the free software 001 Game Creator® to approach the theme of Environmental Education (EE) for students of Technical High School (THS). In addition, Maximum Likelihood (ML) Factor Analysis (FA) was used as an analytical tool to evaluate the results obtained. Ninety students from three THS classes participated in the research, and a questionnaire was applied to collect data on previous EE knowledge and perceptions of the developed game. Given the work carried out, it was possible to show that the ML analysis technique was a skillful and fast tool for understanding the evaluation of educational games, identifying that the application of the game "A ride on the Comptronics" aroused the interest of the students and provided a learning experience. dynamic and pleasurable, in a cooperative and very immersive way.